The Relationship Between Parental Education Level And Dental And Oral Health Parenting In Preschool-Aged Children Aisyiyah 1 Pangkajene Kindergarten Maritengngae District Sidenrenng Rappang Regency In 2023 - sultan, sultan (Journal of health research and technology, 2024)
Teeth in preschoolers are generally still deciduous teeth with tooth structure and morphology that are prone to tooth cavities. The prevalence of dental and oral health problems in preschool-age children is still high due to their wrong brushing habits and the habit of frequently consuming karyogenic foods. In addition, this is where children are still very dependent on parents in terms of maintaining cleanliness and dental health. This study aims to determine the relationship between parents' education level and dental and oral health parenting for preschool children of Aisyiyah 1 Pangkajene Kindergarten, Maritengngae District, Sidenreng Rappang Regency in 2023. This type of study is a correlational descriptive and sampling is a total sampling of 43 child samples using univariate data analysis formulas (percentage, distribution and frequency) and bivariate data analysis formulas (chi square test). Using the square test we get a value of 0.008. Therefore the value of p = 0.008 < (0.05) (α). In the research hypothesis that Ho was rejected and Ha was accepted, which means that there is a relationship between parents' education level and children's dental and oral health parenting.